2008
DOI: 10.1007/s11135-008-9197-4
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the effect of pre-incentives and post-incentives based on draws on response to web surveys

Abstract: Web surveys, Incentives, Draws, Response rate, Quality response,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Overall, psychological distress is measured using the K-6 instrument (Kessler et al, 2003), which is scored on a scale of 0-24. We also use the two K-6 items specific to anxiety (feeling 'nervous' and 'restless or fidgety') as a 6 We chose the $10 cash 'pre-incentive' (not conditional on participation) on the basis of survey methods research generally indicating that this is as effective as 'post-incentives' (awarded only after participation), at least for relatively small amounts (Sanchez-Fernandez et al, 2010). Also, the 'pre-incentive' has the advantage of not requiring an additional letter or email for delivery of the incentive.…”
Section: Survey Data Collection and Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, psychological distress is measured using the K-6 instrument (Kessler et al, 2003), which is scored on a scale of 0-24. We also use the two K-6 items specific to anxiety (feeling 'nervous' and 'restless or fidgety') as a 6 We chose the $10 cash 'pre-incentive' (not conditional on participation) on the basis of survey methods research generally indicating that this is as effective as 'post-incentives' (awarded only after participation), at least for relatively small amounts (Sanchez-Fernandez et al, 2010). Also, the 'pre-incentive' has the advantage of not requiring an additional letter or email for delivery of the incentive.…”
Section: Survey Data Collection and Sample Characteristicsmentioning
confidence: 99%
“… We chose the $10 cash ‘pre‐incentive’ (not conditional on participation) on the basis of survey methods research generally indicating that this is as effective as ‘post‐incentives’ (awarded only after participation), at least for relatively small amounts (Sanchez‐Fernandez et al ., ). Also, the ‘pre‐incentive’ has the advantage of not requiring an additional letter or email for delivery of the incentive.…”
mentioning
confidence: 97%
“…Munoz-Leiva et al (2010) examined how personalization and frequency of reminder mailings can influence response rates for mailing list-based surveys. Sanchez-Fernandez et al (2010) looked at how pre-and post-incentives for surveys affected response rates for mailing list-based surveys. Yet for surveys introduced through face-toface interaction we have been unable to find a study that examines the effects the survey administrator can have on survey response through their interaction with the respondents.…”
mentioning
confidence: 99%
“…In addition, the economic exchange theory (Ryu et al 2006) is supported because cash (Birnholtz et al 2004;van Veen et al 2011) and larger incentives have been found to be more effective (Schaurer et al 2012). Both effects can also be found in telephone surveys (Singer et al 2000;Curtin et al 2007;Sánchez-Fernández et al 2010). However, in their study Bosnjak and Tuten (2003) find that prepaid incentives do not increase completion rates.…”
Section: Effects On Response Ratesmentioning
confidence: 87%